High toughness polystyrene composite material and method for preparing the same

CN122941125APending Publication Date: 2026-10-20ANHUI HAOYUAN CHEM IND GRP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610785853.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]本发明旨在克服现有技术的不足,提供一种高韧性聚苯乙烯复合材料及其制备方法,以解决现有增韧技术中物理共混法增韧相分散不均、界面相容性差、增韧效果与材料刚性难以兼顾,以及化学共聚法线性结构交联点数量有限、能量耗散路径单一、难以实现多级能量耗散的问题

Benefits of technology

1.本发明通过同时引入DA动态共价键和动态酯键,在聚苯乙烯基体中构筑双重动态网络,并采用具有三维树枝状拓扑结构的马来酰亚胺封端的超支化聚合物。实施例结果表明,本发明聚苯乙烯复合材料的缺口冲击强度较对比例提升>240%,断裂伸长率提升>600%,具有显著的增韧效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention discloses a high-toughness polystyrene composite material and its preparation method, belonging to the field of polymer materials technology. This invention aims to solve the problems of difficulty in simultaneously achieving toughening effect and material rigidity, and the single energy dissipation pathway, in existing polystyrene toughening technologies. The composite material of this invention comprises a furan-functionalized styrene-maleic anhydride copolymer and a maleimide-terminated hyperbranched polymer. The preparation method is as follows: first, a furan-functionalized styrene-maleic anhydride copolymer is prepared via free radical copolymerization; then, a maleimide-terminated hyperbranched polymer is prepared via polycondensation and termination reaction; finally, the two are melt-blended, causing the furan groups and maleimide groups to undergo a Diels-Alder reaction, while simultaneously causing the anhydride groups and hydroxyl groups to undergo an esterification reaction, forming a dual dynamic network. After cooling, a high-toughness polystyrene composite material is obtained. This composite material can be used in electronic and electrical appliance housings, automotive interior parts, packaging containers, and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to a high-toughness polystyrene composite material and its preparation method. Background Technology

[0002] Polystyrene (PS) possesses excellent rigidity, electrical insulation, dimensional stability, and processing fluidity, making it widely used in electronics, automotive interiors, and packaging materials. However, the high rigidity of the polystyrene molecular chain and its low notched impact strength make it prone to brittle fracture upon impact, limiting its application in scenarios requiring high impact resistance. Therefore, improving the toughness of polystyrene is an important research direction in this field.

[0003] Existing technologies for toughening polystyrene mainly fall into two categories: physical blending modification and chemical copolymerization modification. Physical blending modification involves melt-blending elastomers (such as polybutadiene, styrene-butadiene-styrene block copolymer SBS, styrene-ethylene-butene-styrene block copolymer SEBS, etc.) or rigid particles (such as nano-silica, calcium carbonate, etc.) with polystyrene. For example, high-impact polystyrene (HIPS) achieves toughening by dispersing a polybutadiene rubber phase within a polystyrene matrix. However, physical blending methods suffer from problems such as uneven dispersion of the toughening phase, poor interfacial compatibility, and excessively high toughening agent dosages, and it is difficult to achieve a balance between toughening effect and material rigidity.

[0004] Chemical copolymerization modification involves copolymerizing functional monomers with styrene, introducing active groups into the polystyrene backbone or side groups to provide reaction sites for further crosslinking or toughening. CN117866343A discloses an elastic, anti-aging polystyrene plastic that introduces furan groups into a styrene copolymer, followed by a reversible Diels-Alder (DA) reaction with a bismaleimide compound to form a dynamic covalent crosslinking network, endowing the material with self-healing properties and certain impact resistance. This technical solution demonstrates the feasibility of DA dynamic covalent bonds in polystyrene systems. However, the above solution still has the following shortcomings: First, this technology uses a linear copolymer structure, resulting in a limited number of crosslinking points and a single energy dissipation path, thus the toughening effect needs further improvement; second, the system relies solely on DA dynamic bonds, making it difficult to achieve multi-level, multi-scale energy dissipation, limiting the toughening effect under high-speed impact; third, the dynamic network formed by the reaction of side-group furan with an added bismaleimide compound has limited space for crosslinking density and network structure regulation.

[0005] To address the aforementioned problems, this invention provides a novel technical solution that aims to improve the toughness of polystyrene materials by constructing a dual dynamic network and a hyperbranched topology. Summary of the Invention

[0006] This invention aims to overcome the shortcomings of existing technologies and provide a high-toughness polystyrene composite material and its preparation method. This addresses the problems in existing toughening technologies, such as uneven dispersion of the toughening phase, poor interfacial compatibility, difficulty in achieving both toughening effect and material rigidity in physical blending, and the limited number of crosslinking points, single energy dissipation path, and difficulty in achieving multi-stage energy dissipation in linear structures of chemical copolymerization.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high-toughness polystyrene composite material, comprising the following components by weight: (1) 65-85 parts of furan-functionalized styrene-maleic anhydride copolymer; (2) 15-35 parts of maleimide-terminated hyperbranched polymer.

[0008] Preferably, the furan-functionalized styrene-maleic anhydride copolymer is 70-85 parts, and the maleimide-terminated hyperbranched polymer is 15-30 parts.

[0009] Preferably, the furan-functionalized styrene-maleic anhydride copolymer satisfies at least two of the following conditions: (a) Number-average molecular weight of 20,000–50,000 g / mol; (b) The mass percentage of anhydride groups is 15% to 25%; (c) The mass percentage of furan groups is 3% to 8%; (d) Glass transition temperature ≥ 140℃; (e) The melt flow rate is 2~10 g / 10min, and the test conditions are 200℃ and 5kg.

[0010] Preferably, the maleimide-terminated hyperbranched polymer satisfies at least two of the following conditions: (i) Number-average molecular weight is 3000~10000 g / mol; (ii) The terminal maleimide has a functionality of 4 to 8; (iii) Intrinsic viscosity ≤ 0.15 dL / g, test temperature 25℃, test solvent N,N-dimethylformamide, test concentration 10 mg / mL; (iv) Thermal decomposition temperature ≥300℃, test conditions are nitrogen atmosphere and 5% weight loss.

[0011] Preferably, the composite material further includes at least one of the following components: antioxidant, lubricant, processing aid, and filler.

[0012] Preferably, the antioxidant is selected from at least one of hindered phenolic antioxidants, phosphite antioxidants, and thioester antioxidants, and the amount added is 0.1 to 1 part.

[0013] Preferably, the lubricant is selected from at least one of metal soaps, fatty acid amides, and hydrocarbon lubricants, and the amount added is 0.1 to 0.5 parts.

[0014] Preferably, the processing aid is selected from at least one of flow modifier and release agent; the amount added is 0.1 to 1 part.

[0015] Preferably, the filler is selected from at least one of calcium carbonate, talc, silica, and silicates, and the amount added is 0 to 10 parts.

[0016] Secondly, the present invention also provides a method for preparing the high-toughness polystyrene composite material, comprising the following steps: Step 1: Preparation of furan-functionalized styrene-maleic anhydride copolymer Styrene, maleic anhydride, and a monomer containing furan groups were dissolved in an organic solvent and subjected to a free radical copolymerization reaction in the presence of an initiator. After the reaction was completed, the copolymer was precipitated, washed, and dried to obtain a furan-functionalized styrene-maleic anhydride copolymer.

[0017] Preferably, the furan-containing monomer is selected from at least one of furfuryl methacrylate, furfuryl acrylate, and furfuryl glycidyl ether.

[0018] Preferably, the organic solvent is selected from at least one of toluene, dipropylene glycol dimethyl ether (DPDM), butanone (MEK), and N,N-dimethylformamide (DMF).

[0019] Preferably, the molar ratio of styrene, maleic anhydride, and furan-containing monomers is (70-80):(15-25):(3-8). Styrene is the main monomer of the copolymer, providing the polystyrene skeleton and rigidity; maleic anhydride introduces anhydride groups, providing reaction sites for the subsequent reaction with the hydroxyl groups of the maleimide-terminated hyperbranched polymer; furan-containing monomers introduce furan groups, providing reaction sites for the subsequent Diels-Alder (DA) reaction with maleimide.

[0020] More preferably, the molar ratio of styrene, maleic anhydride, and furan-containing monomers is 70:25:5. This 70:25:5 molar ratio ensures good processing flowability of the copolymer while providing sufficient density of anhydride and furan functional groups. If the anhydride group content is too low, there are insufficient reaction sites with the hyperbranched polymer, resulting in inadequate crosslinking density; if the anhydride group content is too high, the copolymer's hygroscopicity increases, and processing stability decreases. The furan group content ensures the formation of an effective dynamic crosslinking network in the subsequent DA reaction.

[0021] Preferably, the total mass of the comonomer is the sum of the masses of styrene, maleic anhydride, and the furan-containing monomer.

[0022] Preferably, the initiator is selected from at least one of peroxide initiators and azo initiators, and its dosage is 0.5% to 2% of the total mass of the comonomer. When the initiator dosage is less than 0.5% of the total mass of the comonomer, the free radical generation rate is too slow, the polymerization reaction is incomplete, the monomer conversion rate is low, and the copolymer molecular weight is too high or unevenly distributed. When the dosage is higher than 2% of the total mass of the comonomer, the initiator residue may affect the subsequent dynamic reaction, and the copolymer molecular weight is too low, resulting in decreased mechanical properties.

[0023] More preferably, the initiator is benzoyl peroxide or azobisisobutyronitrile, and its dosage is 1.0% to 1.5% of the total mass of the comonomer. Benzoyl peroxide is a commonly used free radical initiator that can effectively initiate polymerization reactions. Azobisisobutyronitrile is an azo initiator with a low decomposition temperature (approximately 65 to 75°C), which can initiate polymerization under milder conditions and is suitable for temperature-sensitive furan group monomers.

[0024] Preferably, the reaction is carried out under nitrogen protection at a temperature of 75–90°C for 6–12 hours. Below 75°C, the initiator decomposes too slowly, resulting in incomplete polymerization; above 90°C, the furan groups may undergo side reactions. Nitrogen protection prevents oxygen from inhibiting free radical polymerization.

[0025] Preferably, the specific operations of precipitation, washing and drying are as follows: after the reaction in step one is completed, the reaction solution is cooled to room temperature, slowly poured into methanol to precipitate the precipitate, filtered, the precipitate is washed with methanol 2 to 3 times, and then vacuum dried at 60 to 80°C for 12 to 24 hours.

[0026] Step 2: Preparation of maleimide-terminated hyperbranched polymer Pentaerythritol and a diol containing disulfide bonds are subjected to a polycondensation reaction in the presence of an acid catalyst, and a first post-treatment is performed to obtain a hydroxyl-terminated hyperbranched polyester; the hydroxyl-terminated hyperbranched polyester is dissolved in an organic solvent with maleimide acetic acid and reacted in the presence of a dehydrating condensation agent, and a second post-treatment is performed to obtain a maleimide-terminated hyperbranched polymer.

[0027] Preferably, the molar ratio of pentaerythritol to the disulfide-containing diol is 1:3 to 1:5. Pentaerythritol is a tetrafunctional monomer, and the disulfide-containing diol is a difunctional monomer. When the molar ratio of pentaerythritol to the disulfide-containing diol is less than 1:5, the proportion of difunctional monomers is too high, and the polycondensation reaction is prone to forming linear or slightly branched structures, making it difficult to obtain the ideal hyperbranched topology, resulting in insufficient end-group functionality. When the molar ratio is higher than 1:3, the proportion of pentaerythritol is too high, and the reaction system is prone to excessive cross-linking or even gelation, resulting in decreased product solubility and processability. By controlling the molar ratio within the range of 1:3 to 1:5, hyperbranched polymers with suitable branching degree and end-group functionality meeting the requirements (4 to 8) can be obtained.

[0028] More preferably, the molar ratio of the pentaerythritol to the diol containing a disulfide bond is 1:4.

[0029] Preferably, the diol containing a disulfide bond is selected from at least one of bis(2-hydroxyethyl) disulfide, bis(4-hydroxyphenyl) disulfide, and thiodiethylene glycol.

[0030] More preferably, the diol containing disulfide bonds is bis(2-hydroxyethyl) disulfide. Bis(2-hydroxyethyl) disulfide contains dynamic disulfide bonds, which can introduce dynamic response units into the hyperbranched polymer backbone, further enhancing energy dissipation capability. Simultaneously, its dihydroxy structure can undergo a condensation reaction with pentaerythritol to form a hyperbranched topology.

[0031] Preferably, the sum of the masses of the pentaerythritol and the diol containing disulfide bonds is the total mass of the condensation monomer.

[0032] Preferably, the organic solvent in step two is selected from at least one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), and acetonitrile.

[0033] Preferably, the acid catalyst is selected from at least one of p-toluenesulfonic acid, methanesulfonic acid, benzenesulfonic acid, and tetrabutyl titanate, and its amount is 0.5% to 1% of the total mass of the polycondensation monomers. When the amount of acid catalyst is less than 0.5% of the total mass of the polycondensation monomers, the catalytic efficiency is insufficient, the polycondensation reaction rate is too slow, the molecular weight of the hyperbranched polymer is too low, and the functionality does not meet the requirements; when the amount is more than 1% of the total mass of the polycondensation monomers, excess catalyst may remain in the product, affecting the subsequent esterification reaction and the dielectric properties of the final material.

[0034] More preferably, the acid catalyst is selected from p-toluenesulfonic acid. P-Toluenesulfonic acid is a commonly used catalyst in polycondensation reactions and can effectively catalyze esterification reactions.

[0035] Preferably, the specific operation of the first post-treatment is as follows: after the polycondensation reaction is completed, the reaction solution is slowly poured into ice-cold ether to precipitate the precipitate, filtered, the precipitate is washed with ice-cold ether 2 to 3 times, and then vacuum dried at 40 to 60°C for 24 hours to obtain hydroxyl-terminated hyperbranched polyester.

[0036] Preferably, the dehydration condensation agent includes a carbodiimide condensation agent and an acylation catalyst.

[0037] Preferably, the carbodiimide condensing agent is selected from at least one of N,N'-dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and N,N'-diisopropylcarbodiimide, and the acylation catalyst is 4-dimethylaminopyridine.

[0038] Preferably, the molar ratio of the carbodiimide condensing agent to maleimide acetic acid is (1.0~1.5):1, and the amount of the acylation catalyst is 5%~10% of the mass of maleimide acetic acid.

[0039] More preferably, the carbodiimide condensing agent is N,N'-dicyclohexylcarbodiimide, with a molar ratio of 1.2:1 to maleimide acetic acid. N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, as a catalytic system for the esterification reaction of carboxylic acids and hydroxyl groups, can efficiently catalyze the esterification reaction of maleimide acetic acid with terminal hydroxyl hyperbranched polyesters, thereby introducing maleimide end groups.

[0040] Preferably, the specific operation of the second post-treatment is as follows: after the end-capping reaction is completed, the insoluble matter is removed by filtration, the filtrate is slowly poured into ice-cold ether to precipitate, filtered, the precipitate is washed with ice-cold ether 2-3 times, and dried under vacuum at 40-60°C for 24 hours to obtain the maleimide-terminated hyperbranched polymer.

[0041] Step 3: Melt blending The furan-functionalized styrene-maleic anhydride copolymer obtained in step one is mixed with the maleimide-terminated hyperbranched polymer obtained in step two. The mixture is blended in the molten state to allow the furan groups and maleimide groups to undergo a DA reaction, while the anhydride groups and the hydroxyl groups at the end of the hyperbranched polymer undergo an esterification reaction to form a dual dynamic network. After cooling, a high-toughness polystyrene composite material is obtained.

[0042] Preferably, the mass ratio of the furan-functionalized styrene-maleic anhydride copolymer to the maleimide-terminated hyperbranched polymer is 80:20 to 70:30. When the proportion of furan-functionalized styrene-maleic anhydride copolymer is higher than 80:20, the relative content of the hyperbranched polymer is too low, resulting in insufficient crosslinking points for the DA and esterification reactions, an imperfect dual dynamic network, and limited toughening effect. When the ratio is lower than 70:30, the content of the hyperbranched polymer is too high, which may lead to excessive physical entanglement in the system, excessive melt viscosity, and decreased processing fluidity. On the other hand, excessively high crosslinking density will restrict the movement of molecular chains, causing excessive reduction in material rigidity. Within this mass ratio range, the two components can form a moderate dual dynamic network, ensuring sufficient energy dissipation capacity for toughening while maintaining good processing fluidity and material rigidity.

[0043] Preferably, the melt blending temperature is 150~190℃, and the time is 10~30 minutes. When the melt blending temperature is below 150℃, the polymer melt viscosity is too high, the two components are not mixed uniformly, and the rates of DA reaction and esterification reaction are both low, resulting in insufficient formation of the dynamic network. When the temperature is above 190℃, the furan groups may undergo thermal decomposition, and the reversibility of the DA reaction is enhanced, which is not conducive to the stability of the crosslinked network.

[0044] Preferably, the melt blending is carried out in an internal mixer or a twin-screw extruder at a speed of 60-100 rpm.

[0045] Preferably, in step three, at least one of an antioxidant, lubricant, processing aid, and filler is added and melt-blended together with the furan-functionalized styrene-maleic anhydride copolymer and the maleimide-terminated hyperbranched polymer.

[0046] The high-toughness polystyrene composite material of the present invention can be used to prepare injection molded products and extruded products, and is preferably used in fields with high requirements for impact toughness, such as electronic and electrical housings, automotive interior parts, and packaging containers.

[0047] Thirdly, this invention provides a toughening mechanism for high-toughness polystyrene composite materials. The high toughness of polystyrene is achieved by constructing a dual dynamic network and a hyperbranched topology. The toughening mechanism is as follows: 1. Cooperative energy consumption mechanism of dual dynamic networks This invention simultaneously introduces DA (Diels-Alder) dynamic covalent bonds and dynamic ester bonds, forming a dual dynamic network. DA bonds possess high bond energy and can undergo reversible fracture under stress, absorbing a large amount of impact energy; dynamic ester bonds have moderate bond energy and can preferentially fracture at lower stress levels, dissipating energy. The differences in bond energy and reaction kinetics between the two dynamic bonds allow for fracture and recombination at different stress levels and time scales, achieving multi-level, multi-scale energy dissipation and effectively preventing crack propagation.

[0048] 2. Multiple energy dissipation in hyperbranched topologies This invention employs hyperbranched polymers to replace the traditional linear structure. The three-dimensional topology of hyperbranched polymers has numerous branching points and terminal groups, which can form physical entanglement points and cavitation centers within the polystyrene matrix. When the material is subjected to impact, the molecular chain slippage between branching points, the cavitation effect of branching points, and the energy dissipation of terminal groups work together to provide additional energy absorption pathways, further enhancing the toughness of the material.

[0049] 3. Synergy and complementarity of dual networks The DA dynamic covalent network provides strong cross-linking strength, maintaining the structural integrity of the material; the dynamic ester bond network can preferentially break in stress concentration areas, dissipating energy and acting as a sacrificial bond; the physical entanglement provided by the hyperbranched topology further enhances the network's energy dissipation capability. The synergistic effect of these three factors enables the material to significantly improve impact toughness while maintaining high strength and rigidity.

[0050] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention constructs a dual dynamic network in a polystyrene matrix by simultaneously introducing DA dynamic covalent bonds and dynamic ester bonds, and employs a hyperbranched polymer with maleimide end-capsulation possessing a three-dimensional dendritic topology. The results of the examples show that the notched impact strength of the polystyrene composite material of this invention is increased by >240% and the elongation at break is increased by >600% compared to the comparative example, demonstrating a significant toughening effect.

[0051] 2. This invention significantly improves toughness while maintaining the rigidity and heat resistance of polystyrene composite materials. Example results show that the tensile strength and heat distortion temperature of the polystyrene composite material remain at high levels, effectively solving the problem of balancing toughening effect and material rigidity in traditional toughening technologies.

[0052] 3. This invention systematically studies the effects of the mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer, the end-group maleimide functionality of the hyperbranched polymer, the molar ratio of pentaerythritol to disulfide-containing diol, and the melt blending temperature on the toughness, strength, rigidity, and heat resistance of polystyrene composites.

[0053] 4. This invention is prepared by melt blending, which is compatible with existing polystyrene processing technology and is easy to industrialize. Detailed Implementation

[0054] The present invention will be further described below with reference to specific embodiments and comparative examples. It should be noted that these embodiments are only used to illustrate the present invention and should not be regarded as limiting the present invention.

[0055] Example 1 Step 1: Preparation of furan-functionalized styrene-maleic anhydride copolymer Styrene, maleic anhydride, and furfuryl methacrylate were mixed in a molar ratio of 70:25:5 and dissolved in toluene. Benzoyl peroxide (1.2% of the total mass of the comonomers) was added, and the mixture was reacted at 80°C for 7 hours under nitrogen protection. After the reaction was completed, the reaction solution was cooled to room temperature and slowly poured into methanol to precipitate the precipitate. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 70°C for 18 hours to obtain a furan-functionalized styrene-maleic anhydride copolymer.

[0056] Step 2: Preparation of maleimide-terminated hyperbranched polymer Pentaerythritol and bis(2-hydroxyethyl) disulfide were mixed at a molar ratio of 1:4, and p-toluenesulfonic acid (0.8% of the total mass of the condensation monomers) was added. The mixture was heated to 110°C and stirred for 6 hours under nitrogen protection. After the reaction was completed, the reaction solution was slowly poured into ice-cold diethyl ether to precipitate the precipitate. The precipitate was filtered, washed three times with ice-cold diethyl ether, and dried under vacuum at 50°C for 24 hours to obtain a hydroxyl-terminated hyperbranched polyester.

[0057] The above-mentioned hydroxyl-terminated hyperbranched polyester was dissolved in anhydrous DMF, and maleimide acetic acid (1.2 times the molar number of hydroxyl-terminated molecules), N,N'-dicyclohexylcarbodiimide (molar ratio to maleimide acetic acid 1.2:1), and 4-dimethylaminopyridine (8% by mass of maleimide acetic acid) were added. The mixture was stirred at room temperature for 24 hours. After the reaction was completed, the insoluble matter was removed by filtration, and the filtrate was slowly poured into ice-cold diethyl ether to precipitate. The precipitate was filtered, washed three times with ice-cold diethyl ether, and dried under vacuum at 50°C for 24 hours to obtain the maleimide-terminated hyperbranched polymer.

[0058] Step 3: Melt blending The furan-functionalized styrene-maleic anhydride copolymer (75 parts) obtained in step one was mixed with the maleimide-terminated hyperbranched polymer (25 parts) obtained in step two. Antioxidant 1010 (0.5 parts) and lubricant zinc stearate (0.3 parts) were added. The mixture was stirred in an internal mixer at 165°C and 80 rpm for 15 minutes to allow the furan groups and maleimide groups to undergo a DA reaction, while the anhydride groups and the hydroxyl groups at the end of the hyperbranched polymers underwent an esterification reaction to form a dual dynamic network. After cooling and granulation, a high-toughness polystyrene composite material was obtained.

[0059] Example 2 The difference between this embodiment and Example 1 is that the mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer in step three is 80:20, the melt blending temperature is 150°C, and all other conditions are the same as in Example 1.

[0060] Example 3 The difference between this embodiment and Example 1 is that the mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer in step three is 70:30, the melt blending temperature is 180°C, and all other conditions are the same as in Example 1.

[0061] Example 4 The difference between this embodiment and Example 1 is that in step two, the end-group maleimide functionality of the hyperbranched polymer is controlled to be 4 by adjusting the polycondensation reaction time. Specifically, pentaerythritol and bis(2-hydroxyethyl) disulfide are mixed in a molar ratio of 1:4, and p-toluenesulfonic acid (0.8% of the total mass of the polycondensation monomers) is added. The mixture is heated to 110°C and stirred for 4 hours under nitrogen protection, with all other conditions being the same as in Example 1.

[0062] Example 5 The difference between this embodiment and Example 1 is that in step two, the end-group maleimide functionality of the hyperbranched polymer is controlled to be 8 by adjusting the polycondensation reaction time. Specifically, pentaerythritol and bis(2-hydroxyethyl) disulfide are mixed at a molar ratio of 1:4, and p-toluenesulfonic acid (0.8% of the total mass of the polycondensation monomers) is added. The mixture is heated to 110°C and stirred for 8 hours under nitrogen protection, with all other conditions being the same as in Example 1.

[0063] Example 6 The difference between this embodiment and Example 1 is that the molar ratio of pentaerythritol to bis(2-hydroxyethyl) disulfide in step two is 1:3, while the other conditions are the same as in Example 1.

[0064] Example 7 The difference between this embodiment and Example 1 is that the molar ratio of pentaerythritol to bis(2-hydroxyethyl) disulfide in step two is 1:5, while the other conditions are the same as in Example 1.

[0065] Example 8 The difference between this embodiment and Example 1 is that furfuryl acrylate is used instead of furfuryl methacrylate in step one, while all other conditions are the same as in Example 1. The characterization data of the copolymer are shown in Table 1.

[0066] Example 9 The difference between this embodiment and Example 1 is that bis(4-hydroxyphenyl) disulfide is used instead of bis(2-hydroxyethyl) disulfide in step two, while the other conditions are the same as in Example 1.

[0067] Comparative Example 1 The difference between this comparative example and Example 1 is that the mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer in step three is 90:10, while all other conditions are the same as in Example 1.

[0068] Comparative Example 2 The difference between this comparative example and Example 1 is that the mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer in step three is 60:40, while the other conditions are the same as in Example 1.

[0069] Comparative Example 3 The difference between this comparative example and Example 1 is that the melt blending temperature in step three is 140°C, while the other conditions are the same as in Example 1.

[0070] Comparative Example 4 The difference between this comparative example and Example 1 is that the melt blending temperature in step three is 200°C, while the other conditions are the same as in Example 1.

[0071] Comparative Example 5 The difference between this comparative example and Example 1 is that in step two, the end-group maleimide functionality of the hyperbranched polymer is controlled to be 2 by adjusting the polycondensation reaction time. Specifically, pentaerythritol and bis(2-hydroxyethyl) disulfide are mixed at a molar ratio of 1:4, and p-toluenesulfonic acid (0.8% of the total mass of the polycondensation monomers) is added. The mixture is heated to 110°C and stirred for 3 hours under nitrogen protection, with all other conditions being the same as in Example 1.

[0072] Comparative Example 6 The difference between this comparative example and Example 1 is that in step two, a linear maleimide polymer is used instead of the maleimide-terminated hyperbranched polymer (the linear maleimide polymer is prepared by reacting maleimide acetic acid with hydroxyl-terminated linear polyethylene glycol under the same conditions), and all other conditions are the same as in Example 1.

[0073] Comparative Example 7 The difference between this comparative example and Example 1 is that in step one, a styrene-maleic anhydride copolymer without furan groups is used instead of a furan-functionalized styrene-maleic anhydride copolymer, while the other conditions are the same as in Example 1.

[0074] Comparative Example 8 The difference between this comparative example and Example 1 is that the molar ratio of pentaerythritol to bis(2-hydroxyethyl) disulfide in step two is 1:6, while all other conditions are the same as in Example 1.

[0075] Comparative Example 9 The difference between this comparative example and Example 1 is that the molar ratio of pentaerythritol to bis(2-hydroxyethyl) disulfide in step two is 1:2, while all other conditions are the same as in Example 1. During the reaction, the viscosity of the system increased sharply, partial gelation occurred, and the solubility of the product in DMF decreased significantly, making subsequent melt blending difficult.

[0076] Test methods 1. Characterization methods for raw materials and intermediate products In this invention, the maleimide functionality of the end groups of the maleimide-terminated hyperbranched polymer is determined by nuclear magnetic resonance (NMR) spectroscopy (H1N). 1 The method involves determining the function using 1H NMR. Specifically, the hyperbranched polymer is dissolved in deuterated dimethyl sulfoxide (DMSO-d6), and the spectrum is acquired on a 400 MHz NMR spectrometer. The functionality is calculated based on the integral area ratio of the maleimide double bond characteristic peak (approximately 6.8-7.0 ppm) to the polymer backbone characteristic peak.

[0077] Number average molecular weight was determined by gel permeation chromatography (GPC) using polystyrene as a standard and tetrahydrofuran as the mobile phase.

[0078] Intrinsic viscosity was determined using an Ubbelohde viscometer. Maleimide-terminated hyperbranched polymers were dissolved in DMF to prepare five dilute solutions of different concentrations (0.2–1.0 g / dL). The eluent times for both the pure solvent and the solutions of each concentration were measured in a constant temperature water bath at 25℃ ± 0.05℃. Each sample was measured three times, and the arithmetic mean was taken. A graph was plotted with concentration C on the x-axis and specific viscosity η / C on the y-axis. The intrinsic viscosity [η] was calculated by extrapolating to C=0 using the Huggins equation.

[0079] The thermal decomposition temperature (Td) was determined using a thermogravimetric analyzer (TGA) under a nitrogen atmosphere and a heating rate of 10 °C / min, and the temperature at which 5% weight loss was achieved was taken.

[0080] The glass transition temperature was determined using differential scanning calorimetry (DSC). Under a nitrogen atmosphere, the heating rate was 10 °C / min, and the scanning range was from 30 °C to 200 °C. The midpoint temperature of the second heating curve was taken as the glass transition temperature.

[0081] 2. Test methods for the properties of high-toughness polystyrene composite materials (1) Notched impact strength The test was conducted according to GB / T 1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams". A standard cantilever beam impact testing machine was used. The specimen size was 80 mm × 10 mm × 4 mm, with a V-notch and a notch depth of 2 mm. The impact energy was 2.75 J. Five specimens were tested in each group, and the arithmetic mean was taken as the test result.

[0082] (2) Tensile strength and elongation at break The test was conducted according to GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics". Dumbbell-shaped specimens (Type 1A) were used, with specimen dimensions of 150 mm × 10 mm × 4 mm, and a tensile speed of 5 mm / min. Five specimens were tested in each group, and the arithmetic mean was taken as the test result.

[0083] (3) Bending strength and bending modulus The test was conducted according to GB / T 9341-2008 "Determination of Flexural Properties of Plastics". The sample size was 80 mm × 10 mm × 4 mm, the span was 64 mm, and the test speed was 2 mm / min. Five samples were tested in each group, and the arithmetic mean was taken as the test result.

[0084] (4) Heat distortion temperature The test was conducted according to GB / T 1634.2-2019 "Determination of Deformation Temperature of Plastics under Load - Part 2: Plastics and Hard Rubber". The sample size was 80 mm × 10 mm × 4 mm, the applied bending stress was 1.80 MPa, and the heating rate was 120℃ / h. Three samples were tested for each group, and the arithmetic mean was taken as the test result.

[0085] (5) Vicat softening temperature The test was conducted according to GB / T 1633-2000, "Determination of Vicat Softening Temperature (VST) of Thermoplastic Plastics". The A50 method (heating rate 50℃ / h, load 10 N) was used, and the sample size was 10 mm × 10 mm × 4 mm. Three samples were tested for each group, and the arithmetic mean was taken as the test result.

[0086] (6) Melt flow rate The test was conducted according to GB / T 3682.1-2018, "Determination of melt mass flow rate (MFR) and melt volumetric flow rate (MVR) of thermoplastics – Part 1: Standard method". The test conditions were 200℃ and 5 kg. Each sample was tested three times, and the arithmetic mean was taken as the test result.

[0087] Description of characterization data for styrene-maleic anhydride copolymer The furan-functionalized styrene-maleic anhydride copolymers used in Examples 1-7 and 9 were prepared by the method in step one of Example 1, and their characterization data are shown in the first row of Table 1. The copolymer used in Example 8 was prepared by the method in step one of Example 8. The furan-free styrene-maleic anhydride copolymer used in Comparative Example 7 was a commercially available product.

[0088] Table 1 Characterization data of styrene-maleic anhydride copolymer

[0089] Characterization data of maleimide-terminated hyperbranched polymers The maleimide-terminated hyperbranched polymers in each example and comparative example were prepared by the corresponding step two method, and their characterization data are shown in Table 2.

[0090] Table 2 Characterization data of maleimide-terminated hyperbranched polymers

[0091] The performance test data of high-toughness polystyrene composite materials are shown in Table 3.

[0092] Table 3 Summary of performance test data for high-toughness polystyrene composite materials

[0093] Note: Due to the excessively high proportion of pentaerythritol in Comparative Example 9 (molar ratio 1:2), gelation occurred during the polycondensation reaction, and the product could not undergo subsequent melt blending processing. Therefore, no performance test was conducted.

[0094] Results Analysis and Conclusions Comparative Example 7 used a styrene-maleic anhydride copolymer without furan groups instead of a furan-functionalized styrene-maleic anhydride copolymer, resulting in an impact strength of only 2.8 kJ / m. 2 This demonstrates that the introduction of furan groups can form DA dynamic covalent bonds, thereby imparting a toughening effect to polystyrene composites.

[0095] Comparative Example 6, which used a linear maleimide polymer instead of a hyperbranched polymer, showed an impact strength of only 3.8 kJ / m. 2 Maleimide-terminated hyperbranched polymers possess a three-dimensional dendritic topology, with numerous branching points and terminal groups forming physical entanglement points and cavitation centers. During impact, energy is dissipated through chain slip and cavitation effects. This comparative result demonstrates that the energy dissipation capability of hyperbranched topologies is irreplaceable by linear structures.

[0096] The notched impact strength of the samples in Examples 1-9 was 9.5~11.8 kJ / m. 2 Compared to Comparative Example 7, the performance was improved by approximately 240% to 320%; the elongation at break was 11.2% to 19.2%, an improvement of approximately 600% to 1100% compared to Comparative Example 7; the tensile strength was 35.2 to 41.0 MPa, maintaining good rigidity. Among these, the furan-functionalized styrene-maleic anhydride copolymer and the maleimide-terminated hyperbranched polymer of Example 1, with a mass ratio of 75:25, a maleimide end-group functionality of 6 in the hyperbranched polymer, a molar ratio of pentaerythritol to bis(2-hydroxyethyl) disulfide of 1:4, and a melt blending temperature of 165°C, exhibited the best overall performance, with a notched impact strength of 11.2 kJ / m. 2 The tensile strength is 38.5 MPa, the elongation at break is 16.8%, and the heat distortion temperature is 81.5℃.

[0097] By comparing Examples 1-7 with Comparative Examples 1-5 and 8-9, the preferred range of key parameters was established.

[0098] The preferred mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer is 80:20 to 70:30. Beyond this range, the impact strength decreases significantly: in Comparative Example 1, the mass ratio was 90:10, and the impact strength dropped to 5.2 kJ / m. 2 In Comparative Example 2, the mass ratio of the two components was 60:40, and the impact strength was 7.5 kJ / m. 2 .

[0099] The maleimide-terminated hyperbranched polymer preferably has a functionality of 4 to 8; comparative example 5 has an impact strength of only 4.2 kJ / m when the functionality is 2. 2 .

[0100] The preferred molar ratio of pentaerythritol to disulfide-containing diol is 1:3 to 1:5. In Comparative Example 8, when the molar ratio is 1:6, the functionality is only 3 and the impact strength is 6.2 kJ / m. 2 In Comparative Example 9, the molar ratio of the two was 1:2, resulting in gelation and making the samples unprocessable.

[0101] The preferred melt blending temperature is 150~180℃. In Comparative Example 3, the melt blending temperature was 140℃, and in Comparative Example 4, the melt blending temperature was 200℃. The DA reaction was incomplete, and the impact strength decreased to 6.8 kJ / m², respectively. 2 and 6.5 kJ / m 2 .

[0102] While significantly improving toughness, this invention maintains the rigidity and heat resistance of polystyrene composites. Example 1 exhibits a tensile strength of 38.5 MPa and a heat distortion temperature of 81.5°C. Example 2 (with a mass ratio of furan-functionalized styrene-maleic anhydride copolymer to maleimide-terminated hyperbranched polymer of 80:20) shows the highest tensile strength at 41.0 MPa, maintaining good rigidity. Example 3 (with a mass ratio of 70:30) shows the highest elongation at break at 19.2%, demonstrating excellent toughness. This indicates that the dual dynamic network design of this invention effectively solves the problem of balancing toughening effect and material rigidity in traditional toughening technologies.

[0103] Furthermore, in Example 8, furfuryl acrylate was used instead of furfuryl methacrylate, and its impact strength was 10.8 kJ / m. 2 Example 9 uses bis(4-hydroxyphenyl) disulfide instead of bis(2-hydroxyethyl) disulfide, and its impact strength is 10.5 kJ / m. 2 This indicates that different furan-containing monomers and different disulfide-containing diols are applicable in this invention.

[0104] The core innovation of this invention lies in: constructing a dual dynamic network through DA dynamic covalent bonds and dynamic ester bonds to achieve multi-level energy dissipation; and providing more crosslinking points and energy dissipation pathways through a hyperbranched topology. The synergistic effect of these designs enables the polystyrene composite material to maintain high strength and rigidity while significantly improving impact toughness, providing a new technical approach for the development of high-toughness polystyrene materials.

[0105] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A high-toughness polystyrene composite material, characterized in that, By weight, it includes the following components: (1) 65-85 parts of furan-functionalized styrene-maleic anhydride copolymer; (2) 15-35 parts of maleimide-terminated hyperbranched polymer.

2. The high-toughness polystyrene composite material according to claim 1, characterized in that, The furan-functionalized styrene-maleic anhydride copolymer satisfies at least two of the following conditions: (a) Number-average molecular weight of 20,000–50,000 g / mol; (b) The mass percentage of anhydride groups is 15% to 25%; (c) The mass percentage of furan groups is 3% to 8%.

3. The high-toughness polystyrene composite material according to claim 1, characterized in that, The maleimide-terminated hyperbranched polymer satisfies at least two of the following conditions: (i) Number-average molecular weight is 3000~10000 g / mol; (ii) The terminal maleimide has a functionality of 4 to 8; (iii) Intrinsic viscosity ≤ 0.15 dL / g, test temperature 25℃, test solvent N,N-dimethylformamide, test concentration 10 mg / mL.

4. The high-toughness polystyrene composite material according to claim 1, characterized in that, The composite material further includes at least one of the following components: 0.1 to 1 part antioxidant, 0.1 to 0.5 part lubricant, 0.1 to 1 part processing aid, and 0 to 10 parts filler.

5. A method for preparing a high-toughness polystyrene composite material as described in any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Styrene, maleic anhydride, and a monomer containing a furan group are subjected to a free radical copolymerization reaction to obtain the furan-functionalized styrene-maleic anhydride copolymer; Step 2: Pentaerythritol is subjected to a polycondensation reaction with a diol containing disulfide bonds, and then reacted with maleimide acetic acid to obtain the maleimide-terminated hyperbranched polymer. Step 3: The furan-functionalized styrene-maleic anhydride copolymer obtained in Step 1 is melt-blended with the maleimide-terminated hyperbranched polymer obtained in Step 2 to form a dual dynamic network. After cooling, the high-toughness polystyrene composite material is obtained.

6. The preparation method according to claim 5, characterized in that, In step one, the molar ratio of styrene, maleic anhydride and furan-containing monomer is (70~80):(15~25):(3~8), wherein the furan-containing monomer is selected from at least one of furfuryl methacrylate and furfuryl acrylate; the initiator is selected from at least one of peroxide initiator and azo initiator, and its amount is 0.5%~2% of the sum of the mass of styrene, maleic anhydride and furan-containing monomer.

7. The preparation method according to claim 5, characterized in that, In step two, the molar ratio of pentaerythritol to diol containing disulfide bonds is 1:3 to 1:5, and the diol containing disulfide bonds is selected from at least one of bis(2-hydroxyethyl) disulfide and bis(4-hydroxyphenyl) disulfide.

8. The preparation method according to claim 5, characterized in that, In step two, the polycondensation reaction is carried out in the presence of an acid catalyst, the amount of which is 0.5% to 1% of the sum of the mass of pentaerythritol and the diol containing disulfide bonds.

9. The preparation method according to claim 5, characterized in that, In step three, the mass ratio of the furan-functionalized styrene-maleic anhydride copolymer to the maleimide-terminated hyperbranched polymer is 80:20 to 70:30, and the melt blending temperature is 150 to 190°C.

10. The preparation method according to claim 5, characterized in that, The melt blending is carried out in an internal mixer or a twin-screw extruder at a speed of 60-100 rpm.

Citation Information

Patent Citations

  • Elastic anti-aging polystyrene plastic and preparation method thereof

    CN117866343A